2021
DOI: 10.1002/uog.23694
|View full text |Cite
|
Sign up to set email alerts
|

Fetal loss after chorionic villus sampling in twin pregnancy

Abstract: Objective To estimate the chorionic villus sampling (CVS)‐related risk of fetal loss in twin pregnancy after adjustment for chorionicity, nuchal translucency thickness (NT), intertwin discordance in crown–rump length (CRL), maternal demographic characteristics and serum pregnancy‐associated plasma protein‐A (PAPP‐A) and free β‐human chorionic gonadotropin (β‐hCG). Methods This was a multicenter study from eight fetal medicine units in which the leadership were trained at the Harris Birthright Research Centre f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 26 publications
0
34
0
1
Order By: Relevance
“…Our results are similar to those published recently by Elger T et al, who aimed to estimate the chorionic villous sampling (CVS) related risk of fetal loss in twin pregnancies after adjustment for cofounding factors. The authors reported that in twin pregnancies undergoing CVS, there is a trend for an increased risk of fetal loss from CVS after adjustment for maternal and pregnancy characteristics but this does not reach statistical significance [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results are similar to those published recently by Elger T et al, who aimed to estimate the chorionic villous sampling (CVS) related risk of fetal loss in twin pregnancies after adjustment for cofounding factors. The authors reported that in twin pregnancies undergoing CVS, there is a trend for an increased risk of fetal loss from CVS after adjustment for maternal and pregnancy characteristics but this does not reach statistical significance [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was a multicenter cohort study of women with twin pregnancy from eight fetal medicine units in the UK, Spain, Italy, Bulgaria and Portugal, in which the leadership were trained at the Harris Birthright Research Centre for Fetal Medicine in London, UK, and in which the protocols for screening, invasive testing and pregnancy management are similar 5 . At 11-13 weeks, we recorded maternal demographic characteristics and carried out ultrasound examination for, first, determination of gestational age from the measurement of CRL of the larger twin 13 , second, determination of chorionicity from the number of placentae and the presence or absence of the lambda sign at the intertwin membrane-placental junction 14 , third, exclusion of vanishing twin 15 , fourth, diagnosis of major fetal abnormalities 16 , fifth, assessment of intertwin discordance in CRL (difference between the two fetuses expressed as a percentage of the larger one), because a large discordance is associated with adverse pregnancy outcome 10 , and, sixth, measurement of NT in each fetus for assessment of risk for trisomy and determination of whether the NT in one or both fetuses was ≥ 95 th percentile of our reference range for CRL 17 , because high NT is associated with adverse pregnancy outcome 11 .…”
Section: Study Design and Populationmentioning
confidence: 99%
“…Four small studies reported contradictory results concerning the risk of CVS-related miscarriage, as compared to controls that did not undergo invasive testing [1][2][3][4] . The issue of the CVS-related risk of fetal loss was addressed by a recent multicenter study of 8581 twin pregnancies undergoing ultrasound examination at 11-13 weeks' gestation, including 445 twin pregnancies that had CVS 5 . Multivariable logistic regression analysis with backward stepwise elimination was used to examine whether CVS provided a significant independent contribution to the prediction of the risk of fetal loss after adjusting for maternal and pregnancy characteristics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of safety, many studies have demonstrated that CVS is a safe prenatal diagnostic procedure in both singleton and twin pregnancies 7,8 . Patients should be reassured that CVS is not associated with a significant increase in the rate of miscarriage.…”
mentioning
confidence: 99%